(untitled) (Medico Legal Update, 2021)
In this paper, combinations of a ceramic mixture with a polymer were developed to be used as a substitute for damaged bones or teeth. Overlays were prepared using the manual mixing method, followed by the use of ultrasound technology to ensure uniform distribution of the powder within the polymer. The polymer (PMMA) is supported with a ceramic powder (HAMgO) prepared using an effective mechanical mixing method. Where the percentages were used for consolidation, starting from (1%-4%). The results of the tests showed mechanical corrosion or the so-called wear and tear of a significant improvement for the reinforced polymeric compounds as the corrosion rate decreased to less than half at 4%. Likewise, the results of the particle hardness examination showed a successive increase in the percentages compared to the polymer base material. The results of the durability of compressibility and the Yunk coefficient showed a direct increase with the increase in the percentages of the added ceramic powder. The results were interpreted using the scanning electron microscope and by relying on the density values approved from the results of the exercise.